Practices of Municipal Solid Waste Management in Nilai, Negeri Sembilan - Lim, Boon Lek (2015)
Solid waste is waste that is produced either by residential, commercial or industrial sectors of society. Municipal solid waste is mainly produced from residential and commercial sources as domestic waste. Throughout the year, as the population of Malaysia increases drastically the production of municipal solid waste increases as well. Without proper municipal solid waste management, the huge amount of municipal solid waste that is produced will not be able to be treated in a short time and it will damage the environment and also cause uncomfortable surroundings for the public. This report is to investigate the current practice of municipal solid waste management in Nilai Negeri Sembilan by finding out the technique that is being used for their municipal solid waste management and also o evaluate the level of satisfaction amongst the residents toward the current municipal solid waste management provided by SWM Environment Sdn Bhd. In order to carry out the study, a questionnaire was distributed and quantitative analysis was earned out, interviews were also carried out with the local council Majlis Pembandanan Nilai (MPN) and SWM. Environment Sdn Bhd to help in the evaluation of the current municipal solid waste management. At the end of the report, a better management for the municipal solid waste will be proposed for further studies. The results from the questionnaire show that most of the respondents are not satisfied with the efficiency of the garbage truck service provided by the company and also that they feel that the garbage truck does not collect a variety of solid waste. I however, through the interview with the project manager of the SWM Environment Sdn Bhd, it was discovered that the collection of all types of solid waste was carried out weekly but the public did not know the difference between the truck which collects municipal solid waste and the one that collects garden or bulky waste. It also reveals that general public compliance is very important, as the public should know their role and responsibility toward the generation of municipal solid waste. The public can help by sorting out the solid waste before they put it into the bin. Recycling can also help in reducing the production of solid waste, and as some of the unwanted waste is recyclable there will be less landfill area needed. A proper municipal solid waste management is very important as it helps in ensuring the solid waste is taken to a suitable disposal site and also treats the solid waste so it will not cause any damage to the environment.